2012
DOI: 10.1007/s00134-012-2626-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurally adjusted ventilatory assist (NAVA) improves patient–ventilator interaction during non-invasive ventilation delivered by face mask

Abstract: Purpose: To determine if, compared to pressure support (PS), neurally adjusted ventilatory assist (NAVA) reduces patient-ventilator asynchrony in intensive care patients undergoing noninvasive ventilation with an oronasal face mask. Methods: In this prospective interventional study we compared patient-ventilator synchrony between PS (with ventilator settings determined by the clinician) and NAVA (with the level set so as to obtain the same maximal airway pressure as in PS). Two 20-min recordings of airway pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
4
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 31 publications
9
71
4
4
Order By: Relevance
“…A maximum trigger delay of 100 ms, 13,14 corresponding to ϳ12.5% of the mean T I of 800 ms, 4,[15][16][17] is usually considered as acceptable in adult patients. In this study, inspiratory times of 400, 500, and 600 ms to simulate a preterm neonate, a full-term neonate, and a child were used, respectively (hereafter referred to as patient type).…”
Section: Measured Parametersmentioning
confidence: 99%
“…A maximum trigger delay of 100 ms, 13,14 corresponding to ϳ12.5% of the mean T I of 800 ms, 4,[15][16][17] is usually considered as acceptable in adult patients. In this study, inspiratory times of 400, 500, and 600 ms to simulate a preterm neonate, a full-term neonate, and a child were used, respectively (hereafter referred to as patient type).…”
Section: Measured Parametersmentioning
confidence: 99%
“…NAVA has also been described in NIPPV. [20][21][22] Summary The goal of positive pressure ventilation is to provide respiratory support, while decreasing the potential for harm. Approaches such as volume ventilation, NAVA, and noninvasive ventilation techniques help achieve adequate gas exchange while possibly optimizing patient-ventilator interaction.…”
Section: Noninvasive Ventilation and Surgical Patientsmentioning
confidence: 99%
“…2 Adult and pediatric studies showed that NAVA increases breath-to-breath variability and improves patient-ventilator synchrony and patient comfort. [3][4][5][6][7][8][9] This last improvement is also effective in NIV in adult and pediatric subjects 10,11 and in very low birthweight infants, even in the presence of large leaks. 12 To our knowledge, no previous study was designed to evaluate this ventilation mode exclusively in the postoperative period after cardiac surgery in newborns.…”
Section: Introductionmentioning
confidence: 95%